Advanced biofuel technologies status and barriers - Timilsina, Govinda R. (The World Bank, 2010)
Large-scale production of crop based (first generation) biofuels may not be feasible without adversely affecting global food supply or encroaching on other important land uses. Because alternatives to liquid fossil fuels are important to develop in order to address greenhouse gas mitigation and other energy policy objectives, the potential for increased use of advanced (non-crop, second generation) biofuel production technologies has significant policy relevance. This study reviews the current status of several advanced biofuel technologies. Technically, it would be possible to produce a large portion of transportation fuels using advanced biofuel technologies, specifically those that can be grown using a small portion of the world's land area (for example, microalgae), or those grown on arable lands without affecting food supply (for example, agricultural residues). However, serious technical barriers limit the near-term commercial application of advanced biofuels technologies. Key technical barriers include low conversion efficiency from biomass to fuel, limits on supply of key enzymes used in conversion, large energy requirements for operation, and dependence in many cases on commercially unproven technology. Despite a large future potential, large-scale expansion of advanced biofuels technologies is unlikely unless and until further research and development lead to lowering these barriers